THE INFLUENCE OF BLENDED LEARNING ON STUDENT LEARNING OUTCOMES IN GEOGRAPHY IN CLASS XI IPS SMA NEGERI 2 TEMBILAHAN INDRAGIRI HILIR REGENCY, RIAU PROVINCE - Ningsih, Siti Rahayu; rahmanelli, rahmanelli (DEPARTEMEN GEOGRAFI FIS UNP, 2025)
ABSTRACT The purpose of this study is to analyze and describe the effect of blended learning on the academic achievement of grade XI social studies students at SMA Negeri 2 Tembilahan. Learning geography subjects tends to be boring for students because it is still carried out conventionally at SMA Negeri 2 Tembilahan, while two-thirds are below KKM (65), including XI IPS1 has an average of 62, XI IPS2 is 63, and XI IPS3 is 74. The method used is quantitative with a population of 60 people consisting of three classes with a sample of 20 experimental class people and 1 control class person. The results proved the value of Asymp. Sig. (2-tailed) 0.74 > 0.05 (meaning normally distributed), significance value/probability value > 0.05 (meaning the variance of pre-test and post-test results is the same), T-test results > T-table, 9,602 > 1,711 (meaning the hypothesis of this study is accepted), Sig 2 tailed is valued at 0.000 < 0.05 which means that blended learning is significant in Keywords: Blended Learning, Student Learning Outcomes, Geography Lessons, Senior High School